Synchronizing Brazilian Sign Language (LIBRAS) on videos for Open Digital TV with educational purposes - Oliveira, Celso Socorro [UNESP]; Dos Santos Jr., Edson Benedito [UNESP]; Oliveira, Hilda Carvalho de [UNESP] (My University, 2010)
The TV is a potential midia of communication that affects all social classes and it is available in 98% of Brazilian homes. It has been used as a distributor of educational materials since the 1950s. By 2016 the Open Digital TV (ODTV) in Brazil might cover the entire national territory, replacing the TV with analog signals. Concerns about accessibility for People with Special Needs (PSN) in that media have become more intense since the 1990s worldwide. In Brazil, it is estimated 24.6 million of PSN, 23% of them having some type of hearing loss. Of these, 2.9% are reported as deafs. Brazilian Sign Language (LIBRAS) is considered the first literacy language for deaf people in Brazil. In this context, this paper presents a proposal to facilitate the generation of educational content for ODTV based on two components. One is called SynchrLIBRAS and allows subtitles synchronization in Portuguese and a LIBRAS translator window of videos downloaded from the Web. The second component allows the visualization of this content through the Brazilian System of Digital TV and IPTV - environments that implement the middleware Ginga-NCL. The main focus of this paper is the presentation of the first component: SynchrLIBRAS. This proposal has educational purposes, contributing to teach LIBRAS to people who may collaborate with social inclusion of the deaf people.
Keywords: Accessibility; Closed caption; Deaf; Digital TV; IPTV; LIBRAS; Audition; Computer graphics; Information science; Mathematical techniques; Middleware; Teaching; User interfaces; Visualization; Television broadcasting